LAYANAN BIMBINGAN KELOMPOK DENGAN TEKNIK SELF MANAGEMENT TERHADAP KEMATANGAN KARIER PADA SISWA SMA - Tika Nurhayati; R.Ika Mustika; Siti Fatimah (IKIP Siliwangi, 2021)
Career maturity is one of the most important aspects in adolescent development, especially high school students (SMA) are in the exploration stage, namely the search for identity to make mature career decisions. However, there are still many high school students who do not have good career maturity. Therefore, guidance and counseling teachers are expected to guide students in determining their careers, one of which is group guidance usingtechniques self-management. This study uses a qualitative approach with descriptive methods. The data collection techniques used were observation and interviews. The results showed that the condition of the student's career maturity began to grow, due to the handling provided by the counseling teacher through a series of services, one of which was group guidance services with self-management techniques. Keywords: career maturity, self management.